Reflection and transmision of a Bleustein-Gulayev surface wave by the edge of a piezoelectric material - KIEŁCZYŃSKI, P.; PAJEWSKI, W. (Archives of Acoustics, 1986)
The paper presents an analysis of the effect of reflection and transmission of a BLEUSTEIN-GULAYEV transverse surface wave by an edge of a piezoelectric area formed by two mechanically free and electrically shorted planes intersecting at an angle θ. The fundamental properties of the B-G waves have been discussed, as well as the possibilities of their application. A method of calculating the coefficients of reflection, A_R, and transmission, A_T, for a B-G wave by a metallized piezoelectric edge of a 6 mm symmetry, has been presented schematically. The values of coefficients |A_R|^2 and |A_T|^2 were measured in LiJO_3 crystal samples. Suggestions concerning further research on the analyzed effect have been inducted in the conclusions.